International Approaches to Teaching and Learning: A Comprehensive Curriculum Framework - Sadia A Ghaffar, Zubaida Shaheen, Qudsia Nawaz, Munnaza Andleeb, Bushra Subuktageen, Junaid Sarfaraz Khan (Pakistan Journal of Medical & Health Sciences, 2023)
All over the world, students come from various cultures, classes, regions and languages. At the same time, they are interconnected through globalization which calls for education systems to evolve accordingly. The needs of students have divided educators into focuses where there is a genuine need for classroom curriculums at all levels, specially grade school, to foster inclusivity without handing success on a silver plate. Furthermore challenge nations by gearing them up wisely with rather more than basic joint competencies such as social interaction skills necessary in this new 21st Century world. The scope set within this review covers every inch around the globe to make note of country concerns and actions under education policies perhaps changing centuries-old teaching customs while paying attention to their comprehensive curriculum design for transcending global competences. In addition, research has made note on issues along with possibilities in advancing these methods within boundaries of prevailing educational systems. It aims services towards educators along with authorities marking out plans focusing on versatile curriculum frameworks foreshadowing leaps within student engagement transforming classrooms into lifetime cosms welcoming learning and bracing responsible citizenship.